KAJIAN KINERJA OPERASIONAL KERETA API JENGGALA JURUSAN MOJOKERTO – SIDOARJO - Wicaksono, Achmad; Bowoputro, Hendi; Nurdiansyah, Irfan (Jurnal Mahasiswa Jurusan Teknik Sipil, 2017)
On November 24, 2014 PT.KAI (Persero) inaugurated Jenggala train with Mojokerto - Sidoarjo route in order to meet the mobility needs of the areas. To find out the performance of the Jenggala train, it needs to be reviewed in terms of travel time, stop time, time delay, load factor, and cross capacity. It is also necessary to review the service facility for passengers to find out the level of satisfaction on Jenggala train. In this study using survey as a method to get primely data related to operational performance in the form offield survey, and to know customer satisfaction using quisoner with Importance Performance Analysis (IPA) method. The analysis used for the travel time, stop time, and delay time is the 1 tail t-test, load factor using Vukan R Vuchic capacity calculation, route capacity by using scott formula, and customer satisfaction using Importance Performance Analysis (IPA) method. The result of the analysis showed that the average travel time from Mojokerto is 48 minutes at Jenggala 294 and from sidoarjo is 54 minutes at Jenggala 289, the average stop  time from Mojokerto is 3minutes atJenggala 288 and from Sidoarjo is 10 minutes at Jenggala 289, the average of time delay on departure and arrival from Mojokerto is 6 minutes and 5 minutes, while from Sidoarjo is 3 minutes and 3 minutes. The highest Load Factor from Mojokerto is 63.95% and from Sidoarjo is 63,57%. Cross capacity on Mojokerto – Tarik stastion is 56 trains / day and cross capacity at  Sidoarjo – Tulangan is 79 train / day,  with the result of user satisfaction level is 89.34%. Keywords: Railway, Jenggala, Operational Performance, Cross Capacity, IPA